The Legal Perspective Tug-Of-War In Determining The Status Of Loot Boxes And Gacha As Gambling - Susilo, Sigit Agung; Muthia, Serva (JURNAL HUKUM SEHASEN, 2025)
The evolution of technology in the gaming industry has introduced monetization mechanisms such as lootboxes and gacha, which leverage elements of chance. Although popular, these practices raise concerns about potential gambling and their impact on consumers, particularly children. This study aims to analyze the relevance of Indonesian regulations in governing lootboxes and gacha and identify existing regulatory gaps. A normative juridical method was applied by reviewing primary laws such as the ITE Law, the Criminal Code, and consumer and child protection laws. The findings reveal that while existing laws prohibit gambling, they do not explicitly regulate lootboxes. It concludes that more specific regulations and the establishment of a supervisory authority are necessary to protect consumers from digital exploitation.